Window on Asia - Latif, Shahed (Dhaka, Bangladesh : Academic Press and Publishers Limited, 2003)
Collection of articles written by columnist Shahed Latif in his column, Window on Asia, in the Daily Star.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Social conditions